2015
DOI: 10.3109/17453674.2015.1019782
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase treatment of Dupuytren’s contracture using a modified injection method

Abstract: Background and purpose Treatment of Dupuytren’s contracture (DC) with collagenase Clostridium histolyticum (CCH) consists of injection followed by finger manipulation. We used a modified method, injecting a higher dose than recommended on the label into several parts of the cord, which allows treatment of multiple joint contractures in 1 session and may increase efficacy. We studied the occurrence of skin tears and short-term outcome with this procedure.Patients and methods We studied 164 consecutive hands wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…A hand surgeon injected collagenase into the cord using a modified method (Atroshi et al. 2015). After reconstituting collagenase with 0.39 mL of diluent, the surgeon injected all reconstituted collagenase (approximately 0.80 mg) in the cord, distributed in multiple spots along the palpable cord, from the PIP joint to the palmar crease.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hand surgeon injected collagenase into the cord using a modified method (Atroshi et al. 2015). After reconstituting collagenase with 0.39 mL of diluent, the surgeon injected all reconstituted collagenase (approximately 0.80 mg) in the cord, distributed in multiple spots along the palpable cord, from the PIP joint to the palmar crease.…”
Section: Methodsmentioning
confidence: 99%
“…Skin tears after the manipulation procedure were treated with simple dressing and nurse follow-ups, as described previously (Atroshi et al. 2015). The patients returned to the hand therapist after 1 week for splint adjustment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 A previous study has shown that patients treated with collagenase injection for recurrence after surgical fasciectomy had a mean improvement of 43° (SD 28) in total extension deficit. 39 To be able to show a difference of at least 20° in total extension deficit between the groups at 3 months with a SD of 25, alpha level of 0.05 and statistical power of 80%, a sample size of 50 patients (25 per group) will be needed. We aim to recruit 56 patients to account for any potential loss to follow-up.…”
Section: Methods and Analysismentioning
confidence: 99%
“…In the treatment of Dupuytren's disease (DD), the use of Collagenase Clostridium Histolyticum (CCH) represents a new therapeutic alternative for this condition which currently has no definitive cure. Since the publication of the study by Hurst et al [1] in which the immediate clinical results were very positive, several studies have validated the efficacy of CCH using different drug administration protocols with the same safety values [2][3][4][5]. Clinical results appear promising, with recurrence rates similar to those after surgery [6].…”
Section: Editorialmentioning
confidence: 99%